RECCE: SMALL TEAM MISSIONS BEHIND ENEMY LINES - Stadler, Koos (Scientia Militaria - South African Journal of Military Studies, 2015)
Recce: Small team missions behind enemy lines is an autobiography by Colonel (retired) Koos Stadler. The book mainly covers his career as a Special Forces officer and reconnaissance soldier during South Africa’s so-called Border War in Namibia (formerly South West Africa) and Angola, and his involvement in operations against the South West African People’s Organisation (SWAPO) and its military wing, the People’s Liberation Army of Namibia (PLAN). It also covers operations against the African National Congress (ANC) and Angolan forces.